Serum iron as a biomarker for “penumbra freezing” in patients with acute ischemic stroke - Zhang, Xianwen; Xu, Zhiyao; Li, Linyan; Deng, Huimin; Zhou, Qiang; Liu, Jianyu; Liu, Hua (Frontiers in Neuroscience, 2026)
BackgroundIdentifying salvageable penumbra is crucial for revascularization in acute ischemic stroke (AIS) patients presenting beyond standard therapeutic windows. Dysregulated iron metabolism and ferroptosis play significant roles in the pathophysiology of cerebral ischemia. This study aimed to investigate serum iron as a biomarker for identifying the “penumbra freezing” (PF) phenomenon in AIS patients who present beyond the conventional time window.MethodsThis study included patients with AIS presenting late (beyond 4.5-h treatment window). Participants were classified into PF and absence of PF (APF) groups based on CT perfusion and EXTEND trial criteria. Multivariable regression analyzed associations with PF, and diagnostic accuracy was evaluated via ROC curves.ResultsA total of 141 AIS patients were finally included (Age: 71.16 ± 12.37, 54% male). Serum iron levels were significantly lower in the PF group compared with the APF group (8.59 ± 4.34 μmol/L vs. 11.54 ± 6.37 μmol/L, p = 0.04). The initial ROC analysis yielded an AUC of 0.63 (95% CI: 0.48–0.79, p = 0.09). After adjustment for confounders, the model’s AUC improved significantly to 0.76 (95% CI: 0.63–0.89, p < 0.01).ConclusionSerum iron levels correlate with the PF phenomenon in AIS patients beyond the time window, potentially serving as an auxiliary biomarker to aid in identifying suitable candidates for delayed reperfusion therapy. This indicator offers convenient and rapid detection with clinical translation potential, though further validation in prospective, multicenter, large-scale studies remains necessary.